Comparison of Phacoemulsification Cataract Surgery with Low versus Standard Fluidic Settings and the Impact on Postoperative Parameters. Issue 1 (January 2017) - Chang, Anthony; Fridberg, Alexander; Kugelberg, Maria
Purpose: To compare complications after cataract surgery using 2 different phacoemulsification fluidic settings. Methods: One cataract surgeon (M.K.) performed phacoemulsification cataract surgery in one eye of 43 patients in this randomized prospective clinical study conducted at St. Erik Eye Hospital, Stockholm, Sweden. The patients were randomized to phacoemulsification with low fluidic settings in one group and standard fluidic settings in the other group. Corrected distance visual acuity (CDVA), central corneal thickness (CCT), endothelial cell density (ECD), anterior chamber flare, intraocular pressure (IOP), and macular thickness were measured preoperatively and postoperatively, with a final evaluation at 3 months. Surgical time, ultrasound energy, and amount of balanced saline solution used intraoperatively were recorded. Results: Twenty-one patients were included in the group with standard settings and 22 patients were in the group with low settings. There were no significant differences between the groups in CDVA, CCT, flare, IOP, macular thickness, or ECD at 1 day, 3 weeks, or 3 months postoperatively. The surgical time was significantly (p = 0.009) longer and cumulative dissipated energy was significantly (p<0.001) higher in the group with low fluidic settings. Conclusions: Although the surgical time and ECD were significantly higher in the group with low fluidic settings, there were no differences in the CCT, ECD, macular thickness, or inflammation postoperatively between the low and standard fluidic settings during phacoemulsification.